Antioxidant Activity of Vitamin E Concentrate from Magnesium Salts of Palm Fatty Acid Distillate (Mg-PFAD) - Dianika Lestari; Khalisa Putri Aqilah; Salsafia Putri; Ardiyan Harimawan; Diky Mudhakir; Muhamad Insanu (Dept. of Chemical Engineering, Diponegoro University, 2021)
Vitamin E concentrate was produced through saponification of palm fatty acid distillates (PFAD) and magnesium oxide to form Mg-PFAD, followed by three-stages vitamin E extraction with isopropanol, hexane, or ethanol. The vitamin E-rich extracts were evaporated to remove solvent and produced vitamin E concentrate. The objectives of this research were to investigate the effect of organic solvent’s types and solvent to Mg-PFAD mass ratios on vitamin E concentration, solvent selectivity, and antioxidant activity of the vitamin E concentrate. Vitamin E concentrates obtained after isopropanol extraction had vitamin E concentration of 784 ppm with vitamin E recovery of 16 mg tocopherol/100 mg tocopherol in Mg-PFAD, while vitamin E concentrates obtained after hexane extraction had vitamin E concentration of 574 ppm with vitamin E recovery of 35 mg tocopherol/100 mg tocopherol in Mg-PFAD. Isopropanol extraction produced vitamin E concentrate with the highest selectivity for vitamin E and the highest antioxidant activity of 79% IC. It was found that vitamin E concentration was not proportional to the antioxidant activity of the vitamin E concentrate.Keywords: Direct solvent extraction, palm fatty acid distillate, saponification, vitamin E, unsaponifiable matter